Preparation of porous Al2O3 ceramics with enhanced properties by SLS using Al2O3 poly-hollow microspheres (PHMs) coated with CaSiO3 sintering additive. Issue 17 (1st December 2020) - Wu, Jia-Min; Li, Meng; Liu, Shan-Shan; Shi, Yu-Sheng; Li, Chen-Hui; Wang, Wei
Abstract: The mechanical properties of porous ceramics prepared by poly-hollow microspheres (PHMs) is usually low because of the weak bonding between different ceramic PHMs. In this paper, CaSiO3 were coated to the surface of Al2 O3 PHMs through co-precipitation method as sintering additive to improve the properties of Al2 O3 poly-hollow microsphere ceramics (Al2 O3 PHM ceramics). The influence of different amount of CaCl2 solution on properties of the Al2 O3 PHM ceramics such as phase composition, microstructure, porosity and mechanical properties were studied. The porosity of the Al2 O3 PHM ceramics decreased from 77.03% to 68.16% with the increase of CaCl2 solution amount, while compressive strength increased 29 times from 0.29 MPa to 8.39 MPa. The addition of the CaSiO3 could decrease the sintering temperature of Al2 O3 PHM ceramics and significantly improve the mechanical properties of Al2 O3 PHM ceramics, which is beneficial for preparing highly porous Al2 O3 PHM ceramics with high mechanical properties and complex shapes.